Clinical advances and challenges associated with TCR-T cell therapy for cancer treatment - Li, Jianing; Zhang, Yongsheng; Fu, Tong; Xing, Guoli; Cai, Hongbo; Li, Kaiqing; Xu, Yutong; Tong, Ying (Frontiers in Immunology, 2024)
Background: T cell receptor (TCR)-T cell therapy is an innovative form of cancer immunotherapy that genetically modifies patients' T cells to target and destroy cancer cells. However, the current status of clinical trials of TCR-T cell therapy for the treatment of cancer remains unclear. This study aimed to comprehensively analyze the registration trials related to TCR-T cell therapy for the treatment of cancer. Methods: A comprehensive search was conducted in the Trialtrove database for all clinical trials related to TCR-T cell therapy registered by August 1, 2024. Inclusion criteria focused on trials targeting TCR-T cell therapy for oncology, and excluded observational studies and incomplete data. Statistical analysis was performed on key trial characteristics, with between-group comparisons utilizing chi-square or Fisher’s exact tests. Results: Analysis of 174 eligible clinical trials revealed that TCR-T cell therapy exhibits significant efficacy across various tumor types, particularly in refractory hematologic malignancies and certain solid tumors. Additionally, combining TCR-T cell therapy with other immunotherapies enhanced these anti-tumor effects. Conclusion: TCR-T cell therapy holds substantial promise for cancer treatment. Future research should focus on optimizing treatment protocols, enhancing efficacy, and minimizing prices to fully realize the potential of this therapy.